2002
DOI: 10.1016/s0731-7085(02)00147-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of a nitroderivative of acetylsalicylic acid (NCX4016) by rat liver: LC and LC–MS studies

Abstract: The metabolism of a nitroderivative of acetylsalicylic acid, benzoic acid, 2-(acetyloxy)-3-[(nitrooxy)methyl]phenyl ester (NCX4016), the lead compound of a new class of NO-releasing non steroidal-antiinflammatory drugs has been studied in vitro in rat liver subcellular fractions (S 9000 × g, microsomes, cytosol). Samples were extracted with CH 3 CN (2 vol.) containing 1% H 3 PO 4 (2 M), vortexed for 3 min and then centrifuged for 5 min at 5000 rpm. Supernatants were diluted with 0.02 M phosphoric acid and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…In vitro studies have shown that NO-aspirin inhibits COX-1 and COX-2, and that the presence of the spacer and NO-donating moiety in the molecule slows the kinetics of COX-1 inhibition by NCX 4016 compared with aspirin (34). The positional isomer of NO-aspirin used in this study (meta) is converted essentially into salicylic acid, 3-hydroxybenzylalcohol, and a conjugated product between glutathione and the aromatic spacer linking the aspirin moiety to the NOreleasing group (35,36). In rats, following a single administration of NO-aspirin, the main metabolites in plasma were NO x , salicylic acid, and nitrosothiols, with no intact drug observed.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro studies have shown that NO-aspirin inhibits COX-1 and COX-2, and that the presence of the spacer and NO-donating moiety in the molecule slows the kinetics of COX-1 inhibition by NCX 4016 compared with aspirin (34). The positional isomer of NO-aspirin used in this study (meta) is converted essentially into salicylic acid, 3-hydroxybenzylalcohol, and a conjugated product between glutathione and the aromatic spacer linking the aspirin moiety to the NOreleasing group (35,36). In rats, following a single administration of NO-aspirin, the main metabolites in plasma were NO x , salicylic acid, and nitrosothiols, with no intact drug observed.…”
Section: Discussionmentioning
confidence: 92%
“…Although the use of NSAIDs is limited by their gastrointestinal (GI) and renal toxicity, NOreleasing NSAIDs were shown to exert antiinflammatory and analgesic effects that were at least as potent as those of the parent drug, without causing GI tract toxicity (16)(17)(18)(19). The in vivo metabolism of these drugs has been established reasonably well in a rat model (14,20), except that the precise mechanism by which NO is released from the nitro moiety has yet to be understood. NCX-4016 is metabolized by esterases in the liver cells and in plasma to salicylic acid and 3-(nitrooxymethyl)phenol, which is rapidly metabolized to 3-hydroxybenzylalcohol and NO (20).…”
Section: Effect Of Ncx-4016 On the Clonogenecity Of Hoccsmentioning
confidence: 99%
“…The in vivo metabolism of these drugs has been established reasonably well in a rat model (14,20), except that the precise mechanism by which NO is released from the nitro moiety has yet to be understood. NCX-4016 is metabolized by esterases in the liver cells and in plasma to salicylic acid and 3-(nitrooxymethyl)phenol, which is rapidly metabolized to 3-hydroxybenzylalcohol and NO (20). The carbon atom of 3-(nitrooxymethyl)phenol can react with GSH to form 1-(glutathion-S-yl)methylene-3-hydroxybenzene.…”
Section: Effect Of Ncx-4016 On the Clonogenecity Of Hoccsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the previous NO-donor aspirins that seem to require enzymatic metabolism for NO release, [10][11][12] these products proved to release NO under the action of thiols. 13 Intracellular release induced by glutathione is potentiated by ascorbic acid.…”
Section: Introductionmentioning
confidence: 79%